Developing a Teaching Model to Enhance Computational Thinking for Higher Vocational College Students - Kong, Yiyan; Chookhampaeng, Chowwalit (Journal of Ecohumanism, 2024)
The goals of this study were: 1) to study the problems and teaching needs of enhancing computational thinking for higher vocational college students. 2) to develop a teaching model to enhance computational thinking for higher vocational college students. 3) to study the effectiveness of implementing the teaching model to enhance computational thinking for higher vocational college students. The samples were 86 students and 3 teachers in the preliminary survey phase, and 36 students in the implementation phase. Data analysis was done with mean, percentage, standard deviation, content analysis and paired-samples t-test. The research findings showed that the proposed teaching model consisting of eight components and six teaching steps to enhance computational thinking for higher vocational college students. Its significance includes to enhance 4 components of computational thinking: decomposition, pattern recognition, abstraction, algorithm. The experimental students’ post-test scores were statistically significantly higher than the pre-test by .05. The results revealed that, the proposed teaching model can effectively enhance the computational thinking for higher vocational college students. Based on the findings of this study, the researchers recommended that teacher combining new technologies such as AI, to provide students with more scaffolding and teaching support and further investigate the effectiveness of this teaching model in enhancing computational thinking in non-programming teaching.